(untitled) (Revista Contexto & Educação, 2023)
The objective of this study is to analyze the actions resulting from the implementation of guidelines established by the São Paulo State Department of Education, in the context of an integral school, in the public network, according to the speech of a coordinating teacher in the area of Natural Sciences and Mathematics. The instrument used to collect information was an interview conducted with the aid of a semi-structured script, being carried out on the school premises, recorded on audio and later transcribed. To treat and analyze the information collected, we adopted Discourse Analysis, in the French perspective, as presented by Eni Orlandi. The speech of the area coordinating teacher indicates that all the work developed within the school takes place around the Curriculum established by the State Education Secretariat, and the research context is also marked by actions arising from other educational policies, the which have guidelines linked to the Official Curriculum. However, in terms of the incidence of such guidelines, the visibility of instructional insufficiency was increased, as well as the urgent need for collaborative activities that may contribute to the development of professional knowledge, regarding educational policies that should be implemented in school ambience.